2016
DOI: 10.1007/s00268-016-3707-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Access and Survival Amongst British Asians with Pancreatic Cancer

Abstract: This study demonstrates that AAB patients are present with pancreatic cancer at a younger age and that when receiving palliative chemotherapy their survival is significantly better. Further studies and larger data sets over a longer period are required. It is important to examine further the complexity of incidence and survival in ethnic minorities and investigate the underlying reasons when differences are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Isherwood et al reported that Asians/Asian British had higher overall survival and survival for subjects who received palliative therapy (6.1 months and 5.1 months, respectively) compared to White British (4.6 months and 3.7 months, respectively). Median survival in subjects who underwent surgical resection was, however, similar (25.0 months in Asians/Asian British vs. 20.7 months in White British) [39].…”
Section: Discussionmentioning
confidence: 86%
“…Isherwood et al reported that Asians/Asian British had higher overall survival and survival for subjects who received palliative therapy (6.1 months and 5.1 months, respectively) compared to White British (4.6 months and 3.7 months, respectively). Median survival in subjects who underwent surgical resection was, however, similar (25.0 months in Asians/Asian British vs. 20.7 months in White British) [39].…”
Section: Discussionmentioning
confidence: 86%
“…20 A similar cohort result had shown that the overall survival and the survival of patients having palliative treatment were significantly greater in Asian/Asian British compared with White British. 21 Given the highly lethal nature of PC, there is a great urgent need to elucidate the underling mechanisms for the mesenchymal huge difference between the Asian patients and other ethnic populations.…”
Section: Discussionmentioning
confidence: 99%